ATP‐binding cassette transporter A1 (ABCA1) promotes arsenic tolerance in human cells by reducing cellular arsenic accumulation. (April 2014) - Tan, Xiaohua; Yang, Li; Xian, Lingling; Huang, Jin; Di, Chunhong; Gu, Wenyi; Guo, Shuli; Yang, Lei
Summary Arsenic is a toxic element widely distributed in nature, such as water and soil. To survive this metalloid in the environment, nearly all organisms develop strategies to tolerate arsenic toxicity to some degree. Some arsenic‐resistance genes have been identified in bacteria and yeast, but for mammals, especially humans, these genes are largely unknown. The aim of the present study was to identify these genes and benefit our intervention of arsenic resistance. We first established a human arsenic‐resistant ECV‐304 (AsRE) cell line and then used suppression subtractive hybridization and microarray analysis to identify arsenic‐resistant genes in these cells. Of the significantly upregulated genes, three ATP‐binding cassette (ABC) subfamily members, namely ABCA1, ABCE1 and ABCF1, were chosen for further study with RNA interference and overexpression analyses. The 3‐(4, 5‐dimethyl‐2 thiazoyl)‐2, 5‐diphenyl‐2H‐tetrazolium bromide assay was used to determine the cell survival rate and the IC50, whereas atomic fluorescence spectrophotometry was used to determine intracellular arsenic levels. We found that among the three ABC genes, only when ABCA1 gene expression was silenced did cells obviously lose their arsenic tolerance. The arsenic accumulation in ABCA1 deficiency AsRE cells was greater than that in wild type AsRE cells. Overexpression of ABCA1 in HeLa cells decreased arsenic accumulation in the cells and the cells were more resistant to As(III) than control cells transfected with empty vector. These results suggest a new functional role for ABCA1 in the development of arsenic resistance in human cells.